Characterization of the binding of cyanidin-3-glucoside to bovine serum albumin and its stability in a beverage model system: A multispectroscopic and chemometrics study. (1st May 2020) - Hossein Razavizadegan Jahromi, Seyed; Farhoosh, Reza; Hemmateenejad, Bahram; Varidi, Mehdi
Highlights: BSA well interacted with CYG through enthalpy driven hydrogen bonds and van der Waals forces. A tiny amount of BSA could bind all CYG molecules (1:13). Partially unfolded BSA induced by CYG could not change BSA denaturation temperature. The stability of anthocyanins was increased after adding BSA. Abstract: Anthocyanins as one of the main natural groups of food colorants undergo quick color fading, which can be diminished through protein association. The stabilization of cyanidin-3-glucoside (CYG) through binding to bovine serum albumin (BSA) was investigated at pH 3.0 using atomic force microscopy and differential scanning calorimetry along with UV–Vis absorption, steady-state fluorescence, circular dichroism, and three-dimensional emission spectral analyses merged with the multivariate curve resolution-alternative least square method. The stabilized CYG molecules were found at the site II of BSA with combined static and dynamic quenching mechanisms. Approximately 93% of the BSA binding sites were occupied in the BSA-CYG complex through hydrogen bonds and van der Waals forces with the binding constant and stoichiometry ratio of 1.88 × 10 5  M −1 and 1:13, respectively. The results also revealed that CYG molecules caused partial unfolding of the BSA structure, while it was not enough for significant alteration of denaturation temperature. The binding results also indicated that the reduction of H2 O2 -induced-CYG oxidation rate (34.78%) at pH 3.0 was mainly driven via the BSA-hemiketal association, although the colored species of CYG had a greater affinity towards BSA in the equilibrated system at pHs 1.0 and 5.0.